Attendance at prenatal care and adverse birth outcomes in China: A follow-up study based on Maternal and Newborn's Health Monitoring System. (February 2018) - Huang, Aiqun; Wu, Keye; Zhao, Wei; Hu, Huanqing; Yang, Qi; Chen, Dafang
Abstract: Objective: to evaluate the independent association between attendance at prenatal care and adverse birth outcomes in China, measured either as the occurrence of preterm birth or low birth weight. Design: a follow-up study. Setting: the data was collected from maternal and newborn's health monitoring system at 6 provinces in China. Participants: all pregnant women registered in the system at their first prenatal care visit. We included 40152 registered pregnant women who had delivered between October 2013 and September 2014. Measurements: attendance at prenatal care was evaluated using Kessner index. χ 2 tests were used to examine the correlations between demographic characteristics and preterm birth or low birth weight. The associations between attendance at prenatal care and birth outcomes were explored using multilevel mixed-effects logistic regression models. Findings: the prevalence for preterm birth and low birth weight was 3.31% and 2.55%. The null models showed region clustering on birth outcomes. Compared with women who received adequate prenatal care, those with intermediate prenatal care (adjusted OR 1.62, 95%CI 1.37–1.92) or inadequate prenatal care (adjusted OR 2.78, 95%CI 2.24–3.44) had significantly increased risks for preterm birth, and women with intermediate prenatal care (adjusted OR 1.31, 95%CI 1.10–1.55) or inadequate prenatal care (adjusted OR 1.70, 95%CI 1.32–2.19) had significantly increased risks for low birth weight. We found very significant dose-response patterns for both preterm birth (p-trend<0.001) and low birth weight (p-trend = 0.001). Key conclusions and implication for practice: This study shows that attendance at prenatal care in China has independent effects on both preterm birth and low birth weight. Appropriate timing and number of prenatal care visits can help to reduce the occurrence of preterm birth or low birth weight. Highlights: The prevalence of preterm birth and low birth weight are different among northeast, midland and southwest in China. Attendance at prenatal care measured by Kessner index has independent effects on both preterm birth and low birth weight. There are dose-response patterns for attendance at prenatal care and birth outcomes. The greater the lack of attendance at prenatal care, the greater the associations for preterm birth and low birth weight.